2020
DOI: 10.1016/j.cell.2020.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptome Atlas of Murine Endothelial Cells

Abstract: Highlights d A single-cell EC atlas of healthy murine tissues d This study provides an interactive webtool for comparative analyses and data exploration d Characterization of inter-and intra-tissue EC heterogeneity d Discovery tool for characterization of ECs in other datasets

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

63
1,142
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 945 publications
(1,211 citation statements)
references
References 91 publications
63
1,142
3
3
Order By: Relevance
“…Thus CRP may contribute widely to vascular homeostasis, providing a distributed pool of regenerative cells for local vascular maintenance and replenishment. Consistent with this thesis, a recent scRNAseq study also reported rare Apln + “angiogenic” EC in normal tissues 74 .…”
Section: Discussionsupporting
confidence: 76%
“…Thus CRP may contribute widely to vascular homeostasis, providing a distributed pool of regenerative cells for local vascular maintenance and replenishment. Consistent with this thesis, a recent scRNAseq study also reported rare Apln + “angiogenic” EC in normal tissues 74 .…”
Section: Discussionsupporting
confidence: 76%
“…Our data define a human intestinal EC signature that includes almost 150 genes that are enriched in intestinal ECs relative to lung and kidney ECs. Recent work described an adult murine EC atlas spanning 11 organ systems at single cell resolution, and provides a foundational resource to compliment the work presented here, aimed at understanding human intestinal EC patterning (Kalucka et al, 2020). Several of the validated human organ-specific markers identified in our dataset demonstrated similar expression patterns in adult mouse atlas, suggesting that organ-specific signatures established during development are retained into adulthood, although future work should confirm these findings in both developing and adult human and murine tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that vasculature patterning is organ-specific (Daniel et al, 2018; Ding et al, 2010; Feng et al, 2019; Kalucka et al, 2020; Lee et al, 2014; Marcu et al, 2018; Nolan et al, 2013); however, whether or not organoids are programmed with this patterning information in vitro was not known. Furthermore, profiling of organ-specific ECs has not included human intestinal ECs prior to this work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial cells, defined by pan-EC markers PECAM1 , CDH5 and VWF, were highly heterogeneous, consisting of eight subpopulations (Figure 3A). The most abundant subpopulation (53.0% of all EC) was annotated as capillary EC (EC_cap) given the enrichment of RGCC and CA4, marker genes of microvascular endothelium in the mouse endothelial cell atlas36 . A separate cluster, expressing endothelial capillary markers, was largely represented by cells ( Supplementary…”
mentioning
confidence: 99%